Urban Water Disinfection and Mortality Decline in Developing Countries - Sonia R. Bhalotra; Alberto Diaz-Cayeros; Grant Miller; Alfonso Miranda; Atheendar Venkataramani (Institute of Labor Economics (IZA), 2017)
Historically, improvements in the quality of municipal drinking water made important contributions to mortality decline in wealthy countries. However, water disinfection often does not produce equivalent benefits in developing countries today. We investigate this puzzle by analyzing an abrupt, large-scale municipal water disinfection program in Mexico in 1991 that increased the share of Mexico's population receiving chlorinated water from 55% to 85% within six months. We find that on average, the program was associated with a 37 to 48% decline in diarrheal disease deaths among children (over 23,000 averted deaths per year) and was highly cost-effective (about 1,310 per life year saved). However, we also find evidence that age (degradation) of water pipes and lack of complementary sanitation infrastructure play important roles in attenuating these benefits. Countervailing behavioral responses, although present, appear to be less important.
Keywords: I18; H41; J11; 330; clean water; chlorination; child mortality; infectious disease; diarrhea; Mexico; cost-effectiveness; sanitation; behavioral responses